Book Review: Proverbs And The Formation Of Character - Lazarus, Patrick Byornjovi; Sualang, Farel Yosua (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
The book Proverbs and the Formation of Character by Dave Bland highlights how the book of Proverbs shapes moral character through practical and relational wisdom. Bland focuses on the often-overlooked section of sentence literature (Proverbs 10–29) and shows that the book of Proverbs has the power to shape virtues such as justice and self-control. With an interdisciplinary approach, he brings together theology, ethics, homiletics, and psychology to show the relevance of Proverbs in modern life. Wisdom in Proverbs is described as the result of a relationship with God and community, and is obtained through dialogue and life experience. Therefore, Dave Bland's critical insight into the character formation of the book of Proverbs in this book is not only oriented toward a dimension of moral rules, but also a process of character growth that takes place through learning adaptation, correction, and openness to guidance from family with community.